(untitled) (Faculty of Education Scientific Journal, 2024)
"The Impact of Religion on Plato’s Idea of Existence" A research in the field of philosophy of religion raises many issues about it.” The most important of which is the relationship between philosophy and religion by determining the impact of the latter on the former in an important period of philosophical history when a founding figure of the philosophical project. The Platonic philosophical vision on the issue of existence and its relationship to religion is examined from two sides in terms of identifying the religious and philosophical data affecting the personality of the philosopher on the one hand, defining the features of the idea of existence, and determining the role of religion in crystallizing this idea on the other hand. This research aims to show the contribution of religion in crystallizing the issue of existence according to Plato and the impact of this thesis in the establishment of later philosophy of religion by focusing on the principle of existence in terms of the way it is presented as a philosophical issue related to the rest of the philosophical issues and as a methodology that determines a mechanism to deal with them to produce for us in the end a philosophical approach worthy of research and reflection.